2009
DOI: 10.5194/bg-6-2759-2009
|View full text |Cite
|
Sign up to set email alerts
|

Above- and below-ground net primary productivity across ten Amazonian forests on contrasting soils

Abstract: Abstract. The net primary productivity (NPP) of tropical forests is one of the most important and least quantified components of the global carbon cycle. Most relevant studies have focused particularly on the quantification of the above-ground coarse wood productivity, and little is known about the carbon fluxes involved in other elements of the NPP, the partitioning of total NPP between its above-and below-ground components and the main environmental drivers of these patterns. In this study we quantify the ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
243
1
9

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(273 citation statements)
references
References 64 publications
20
243
1
9
Order By: Relevance
“…Since NDVI, PV and NPV are known correlates with canopy greenness, leaf cover, and exposed nonphotosynthetic vegetation, respectively (Roberts et al, 1997;Asner et al, 2005;Gamon et al, 1995), our findings highlight the strong degree to which canopy structural and functional variation is linked to regional patterns of geologic, hydrologic, and soil fertility variation in the lowlands. This finding may also reflect reports of widely varying community composition, productivity, and carbon storage throughout the western Amazonian lowlands (Quesada et al, 2012;Asner et al, 2012a;Higgins et al, 2012;Aragão et al, 2009;Girardin et al, 2014;Carvalho et al, 2013;Tuomisto et al, 1995).…”
Section: Discussionmentioning
confidence: 74%
“…Since NDVI, PV and NPV are known correlates with canopy greenness, leaf cover, and exposed nonphotosynthetic vegetation, respectively (Roberts et al, 1997;Asner et al, 2005;Gamon et al, 1995), our findings highlight the strong degree to which canopy structural and functional variation is linked to regional patterns of geologic, hydrologic, and soil fertility variation in the lowlands. This finding may also reflect reports of widely varying community composition, productivity, and carbon storage throughout the western Amazonian lowlands (Quesada et al, 2012;Asner et al, 2012a;Higgins et al, 2012;Aragão et al, 2009;Girardin et al, 2014;Carvalho et al, 2013;Tuomisto et al, 1995).…”
Section: Discussionmentioning
confidence: 74%
“…This has been advanced as an explanation for the observed seasonal swings over the Amazon basin by several studies (Doughty and Goulden, 2008;Asner and Alencar, 2010;Aragão et al, 2009;Brando et al, 2010). However, the observed seasonal changes in LAI are too large to be attributed to a flush of new leaves only (Samanta et al, 2012).…”
Section: Modis Lai Datamentioning
confidence: 99%
“…Their major finding was that wNPP varied dramatically at the regional scale, and that a large part of this regional variation was due to soil type. Using the data available at 10 tropical forest sites in Amazonia, Aragão et al (2009) showed that total NPP ranged between 18.6 and 34.0 Mg ha −1 yr −1 , with a mean of 25.6 Mg ha −1 yr −1 , much greater than recent regional tropical forest estimates (e.g. Luyssaert et al, 2007;Del Grosso et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They however acknowledged that their estimates were based on an indirect estimation of several key components of NPP. For Amazonian forests, Aragão et al (2009) provide a most useful perspective on this question. Their analysis strongly supports Bray and Gorham's (1964) model: total NPP is consistently close to 3.1 times total litterfall.…”
Section: Introductionmentioning
confidence: 99%